(untitled) (Journal of Hama University, 2020)
The objective of the research is to study the effect of consumer satisfaction on repurchase intention by examining the effect of consumer satisfaction dimensions namely emotional satisfaction and cognitive satisfaction on repurchase intention. And to determine the mediating role of emotional satisfaction. A questionnaire was conducted on a convenient sample of restaurant customers in Lattakia city.The study results indicate that there is a positive effect of cognitive and emotional satisfaction on repurchase intention, and a positive effect of cognitive satisfaction on emotional satisfaction. The results indicate also that emotional satisfaction mediates the effect of cognitive satisfaction on repurchase intention